Whole-Genome Sequencing and Comparative Genome Analysis Provided Insight into the Predatory Features and Genetic Diversity of Two Bdellovibrio Species Isolated from Soil - Omotayo Opemipo Oyedara; Aldo Segura-Cabrera; Xianwu Guo; Temidayo Oluyomi Elufisan; Rafael Alejandro Cantú González; Mario A. Rodríguez Pérez (International Journal of Genomics)
Bdellovibrio spp. are predatory bacteria with great potential as antimicrobial agents. Studies have shown that members of the genus Bdellovibrio exhibit peculiar characteristics that influence their ecological adaptations. In this study, whole genomes of two different Bdellovibrio spp. designated SKB1291214 and SSB218315 isolated from soil were sequenced. The core genes shared by all the Bdellovibrio spp. considered for the pangenome analysis including the epibiotic B. exovorus were 795. The number of unique genes identified in Bdellovibrio spp. SKB1291214, SSB218315, W, and B. exovorus JJS was 1343, 113, 857, and 1572, respectively. These unique genes encode hydrolytic, chemotaxis, and transporter proteins which might be useful for predation in the Bdellovibrio strains. Furthermore, the two Bdellovibrio strains exhibited differences based on the % GC content, amino acid identity, and 16S rRNA gene sequence. The 16S rRNA gene sequence of Bdellovibrio sp. SKB1291214 shared 99% identity with that of an uncultured Bdellovibrio sp. clone 12L 106 (a pairwise distance of 0.008) and 95–97% identity (a pairwise distance of 0.043) with that of other culturable terrestrial Bdellovibrio spp., including strain SSB218315. In Bdellovibrio sp. SKB1291214, 174 bp sequence was inserted at the host interaction (hit) locus region usually attributed to prey attachment, invasion, and development of host independent Bdellovibrio phenotypes. Also, a gene equivalent to Bd0108 in B. bacteriovorus HD100 was not conserved in Bdellovibrio sp. SKB1291214. The results of this study provided information on the genetic characteristics and diversity of the genus Bdellovibrio that can contribute to their successful applications as a biocontrol agent.